Plasma levels of matrix metalloproteinase‐9 (MMP‐9) are associated with cognitive performance in patients with schizophrenia - Noriko Kudo; Hidenaga Yamamori; Tamaki Ishima; Kiyotaka Nemoto; Yuka Yasuda; Michiko Fujimoto; Hirotsugu Azechi; Tomihisa Niitsu; Shusuke Numata; Manabu Ikeda; Masaomi Iyo; Tetsuro Ohmori; et al. (Wiley, 2020)
Abstract Aim Matrix metalloproteinase‐9 (MMP‐9) has been shown to modulate synaptic plasticity and may contribute to the pathophysiology of schizophrenia. This study investigated the peripheral levels of MMP‐9 and its association with cognitive functions in patients with schizophrenia to see the possible involvement of MMP‐9 in pathophysiology of schizophrenia, especially in cognitive decline. Methods We measured the plasma levels of MMP‐9 in 257 healthy controls and 249 patients with schizophrenia, including antipsychotic drug-free patients. We also explored the possible association between plasma MMP‐9 levels and cognitive performance in healthy controls and patients with schizophrenia using the Wechsler Adult Intelligence Scale, Third Edition (WAIS‐ III), the Wechsler Memory Scale‐Revised (WMS‐R), and the Rey Auditory Verbal Learning Test (AVLT). Results We found that the plasma levels of MMP‐9 were significantly higher in patients with schizophrenia, including antipsychotic drug-free patients, than in healthy controls. We found a significant negative association between plasma MMP‐9 levels and cognitive performance in controls and patients with schizophrenia. Conclusion Together, these convergent data suggest a possible biological mechanism for schizophrenia, whereby increased MMP‐9 levels are associated with cognitive impairment.